A Note on the Taxonomy and Wood Anatomy of the Indian Corn aceae with Special Reference to the Genus Cornus - Purkayastha, S. K.; Bahadur, K. N. (Indian Forester, 1977)
Corneveceue a heterogeneous family. Except tor the genus Cornus, all other Indian genera previously dealt with under this family have been transferred to small segregate families: Alangium has been shifted to Alangiaceae, Mastixia to Mastixiuceae, Acuba to Aucubaceae, Nyssa to Nyssaceae, Toricellia to Toricelliaceae and Helwingin to Helwinjiaceae. Leaving out the Mastixiaceae, this segregation, on naorphological and wood anatomical grounds, appears to be justified. The persent study indicates that the last named should he regarded as a subfamily Mastixioideae under the Cornaceae. The characteristics and the main pointa or difference between the Cornaceae and the segregate families are discussed. The genua Cornus has been delimited in different ways by various workers, some accepting the genus in a broad sense and dividing it into sub-genera and sections, other sagregating these groups as distinct genera. The characters used for sub-dividing Cornus do not seem to be sufficient for recognising the segregate genera. The genus has, therefore, been divided into 8 sub-genera whose characters are furnished. The distinguishing features of the Indian species together with their relevant synonyms and distribution are also given.